The Relationship between Nutritional Status and Food Intake with the Physical Fitness Level of Athletes at the Samkot Samarinda Football School in 2022 - Annisa Nur Rabiah; Ratnawati; Sepsina Reski (Formosa Journal of Science and Technology, 2022)
The fitness of Indonesian athletes in general is relatively low which ultimately has an impact on achievements that never improve or even worsen at all levels, both at the regional, national and international levels. This study aims to determine the relationship between nutritional status and food intake with the level of physical fitness of athletes at the Samkot Samarinda Football School. This study used an analytic observation design with a cross sectional design. The sample in this study were 50 people aged 13-15 years who were taken by simple random sampling. The statistical test used is the Chi Square test. There is a significant relationship between nutritional status and physical fitness (p=0.011) while in food intake there is no significant relationship between energy intake (p=0.138), protein (p=0.345), fat (p=0.829) and carbohydrates (p = 0.781) with physical fitness. There is a significant relationship between nutritional status and physical fitness. There was no significant relationship between energy, protein, fat and carbohydrate intake with physical fitness in the Samkot Samarinda Football School (SSB) Students.